Cote d'Ivoire : Requests for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2020)
Cote d'Ivoire will be significantly impacted by COVID-19 pandemic: the number of cases in the country has increased rapidly since the first confirmed case was reported on March 11 and the global crisis is expected to severely affect supply chains and external demand. The authorities' policy response to the pandemic has been swift, putting in place measures to help contain and mitigate the spread of the disease and designing a health response plan. They have complemented these steps with an economic package to provide targeted support to vulnerable populations and firms affected by the pandemic. The pandemic will also temporarily dampen domestic revenue mobilization and complicate access to international market financing.